Factors associated with body weight status among students in a Malaysian private university - Mahgoub, Salma Kamaleldien Ali (2016)
Ranking the highest for prevalence of overweight and obesity in South East Asia, Malaysia has a great urgency in responding to the obesity epidemic. This study aimed to determine the predictors of body weight status among students in one of the private university in Malaysia. This was a cross-sectional study conducted among students in Infrastructure University Kuala Lumpur (IUKL) (N=281), between February to April 2015. Data was gathered using questionnaire consisted of seven sections: sociodemographic characteristics, physical activity, environmental factors, emotional eating factors, sleeping quality, weight-control behaviors and a 24-hours recall dietary intake. Weight, height, body mass index (BMI), and waist circumference were measured to determine the body weight status. Chi-square and independent t-test as well as logistic regression were used to determine the predictors of body weight status. It was found that 28.1% of the respondents were overweight and 7.5% were obese while 32.0% at risk of abdominal obesity, making the overall obesity in the range of 32.0% – 35.6%. The prevalence of both overweight/obese significantly differed with transports related (p=0.029) and recreational related PA (p=0.010), easy access to transit (0.013), eating less carbohydrate food (p=0.027) and fat adequacy (p=0.040). Abdominal obesity on the other hand, significantly differed with transports related PA (p=0.029), safety to walk at night (p=0.044), change in type of food eaten (p=0.028), intake of appetite suppressants (p=0.021) and liquid diets (p=0.014), increased cigarette smoked (p=0.007) as well as use of laxatives or enemas (p=0.045). Both the overweight/obesity and abdominal obesity status also differed significantly with problems to control eating certain food (p=0.026 vs p=0.047), fasting (p=0.032 vs 0.032) and energy under-reporting (p=0.030 vs p=0.003). Multiple logistic regression analysis showed that the risk of being overweight/obese was significantly higher among respondents who were of older age (AOR=5.66), did not perform vigorous recreational related PA (AOR=1.94), live in neighborhood that did not maintain sidewalks (AOR=2.97), had moderately worse sleep efficiency (AOR=2.51), always could not control their diet after night work (AOR=2.69) and sometimes as well as generally give up diet and eat again without control, especially fattening food (AOR=3.05 vs 3.14). However, the risk was reduced about 50% among respondents who sometimes eat less carbohydrate food (AOR=0.56). Meanwhile, the risk of abdominal obesity was significantly higher among respondents from lowest income group (AOR=4.71), those who did not perform vigorous recreational related PA (AOR=2.00), under-report energy (AOR=2.80), always reduce the amount of food (AOR=3.81) and sometimes as well as always on liquid diets (AOR= 3.47 vs 9.70). In contrast, the risk was lower about 86-87% among those who always perform fasting and consume appetite suppressants (AOR=0.14 vs 0.13). Overweight/obese status model explained 23.3% of the variation while that of abdominal obesity was 37.2%. This study provides evidence supporting the significant relationship between several environmental factors, emotional eating factor, sleep quality, weight control behavior and energy intake with overweight/obese and abdominal obesity risk. Vigorous recreational related PA was negatively associated with overweight/obesity as well as abdominal obesity which reiterate previously published information.